The Effect and Potential Mechanism of Maternal Micronutrient Intake on Offspring Glucose Metabolism: An Emerging Field - Wu, Yifan; Zhang, Qian; Xiao, Xinhua (Frontiers in Nutrition, 2021)
Diabetes has become the most common metabolic disease around the world. In addition to genetic and environmental factors in adulthood, the early life environment is critical to the progression of diabetes in adults, especially the environment during the fetal period; this concept is called “fetal programming”. Substantial evidence has illustrated the key role of early life macronutrient in programming metabolic diseases. Recently, the effect of maternal micronutrient intake on offspring glucose metabolism during later life has become an emerging field. This review focuses on updated human and animal evidence about the effect of maternal micronutrient status on offspring glucose metabolism and the underlying mechanism.